Comments Regarding the Book How To Avoid A Climate Disaster - VIRGINIA CÂMPEANU (Global Economic Observer)
Climate change and the growing and more frequent global disasters caused by them over the last 30 years have led to the initiation and deployment of global and European climate change strategies based on largescale research. The COVID- 19 pandemic has not stopped concerns in this field, moreover, those have intensified, with many countries setting the target of achieving climate neutrality by 2050. The European Union, through the European Green Deal, is not only a promoter, but also a leader of the global climate change movement. In this context, our article presents some comments regarding a book that was recently published (February 2021), "How to Avoid a Climate Disaster" written by Bill Gates, based on research made by a large group of multi-disciplinary experts, brought together by the Bill & Melinda Gates Foundation and with the financial support of internationally renowned investors. Of the 12 chapters of the book, the author presents synthetically a) the premises from which the research began; b) the solutions to achieve the planet's climate neutrality, and c) the recommendations of the author of the book to reduce the costs involved in combating climate change and achieving zero net carbon in 2050. The recommendations are concrete, as a Medium-Term (2030) and Long-Term (2050) Action Plan and are addressed to governments, parliaments and people around the world.